The Influence of the Reward and Punishment System on Employee Work Discipline at KPKNL Banjarmasin - Nazwa Syifa (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze both the partial and simultaneous effects of reward and punishment systems on employee work discipline at KPKNL Banjarmasin. Using a quantitative approach with a total sampling of 50 employees, the data were processed using multiple linear regression with SPSS version 25. The findings reveal that the reward system significantly and positively affects work discipline, with a t-value of 3.127 > 2.01174 and a significance value of 0.003 < 0.05, supported by a positive coefficient of 0.345. Similarly, the punishment system also has a significant and positive impact, with a t-value of 5.363 > 2.01174 and a significance value of 0.000 < 0.05, with a coefficient of 0.628. Simultaneously, the two variables show a significant effect on work discipline, as indicated by an F-value of 108.766 > 4.05 and a significance level of 0.000 < 0.05. The contribution of reward and punishment systems to work discipline reaches 82.2%, while the remaining 17.8% is influenced by other external factors not explored in this study.